Fertilizer 15N Accumulation, Recovery and Distribution in Cotton Plant as Affected by N Rate and Split - Guo-zheng YANG; Kun-yan CHU; Hao-yue TANG; Yi-chun NIE; Xian-long ZHANG (Journal of Integrative Agriculture, 2013)
N fertilization of 300 kg N ha−1 is normally applied to cotton crops in three splits: pre-plant application (PPA, 30%), first bloom application (FBA, 40%) and peak bloom application (PBA, 30%) in the Yangtze River Valley China. However, low fertilizer N plant recovery (NPR) (30-35%) causes problems such as cotton yield stagnation even in higher N rate, low profit margin of cotton production and fertilizer release to the environment. Therefore, it is questioned: Are these three splits the same significance to cotton N uptake and distribution? An outdoor pot trial was conducted with five N rates and 15N labeled urea to determine the recovery and distribution of 15N from different splits in cotton (Gossypium hirsutum L. cv. Huazamian H318) plant. The results showed that, cotton plant absorbed fertilizer 15N during the whole growing period, the majority during flowering for 18-20 d regardless of N rates (150-600 kg ha−1). Fertilizer 15N proportion to the total N accumulated in cotton plant increased with N rates, and it was the highest in reproductive organs (88% averaged across N rates) among all the plant parts. FBA had the highest NPR (70%), the lowest fertilizer N lose (FNL, 19%), and the highest contribution to the fertilizer 15N proportion to the total N (46%) in cotton plant, whereas PPA had the reverse effect. It suggests that FBA should be the most important split for N absorption and yield formation comparatively and allocating more fertilizer N for late application from PPA should improve the benefit from fertilizer.